Inovasi Pembelajaran Berbasis Teknologi Informasi: Model Discovery Learning Berbantuan Aplikasi Inaturalist Pada Materi Keanekaragaman Hayati : (Innovation of Learning Based on Information Technology: A Model of Discovery Learning Assisted by Inaturalist Applications on Biodiversity Materials) - Anna Argiyanti; Widya Cristanti; Ridho Ilafi Sukma; Riandi Riandi; Bambang Suprianto (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The COVID19 pandemic has resulted in learning loss in students. The problem of learning loss is a concern and there is a need for learning recovery. This study aims to innovate through information technology in the discovery learning model assisted by the iNaturalist application. The research method used is systematic review by collecting evidence to answer the specified research questions. Data collection in this study by reviewing articles in the Google Scholar, SINTA, Scopus databases and books related to keyword model discovery learning and the iNatularist application in English or Indonesian published in 2017 to 2022. The results showed that the innovation of the discovery learning model assisted by the iNaturalist application can be implemented in learning as a way to recover learning after the pandemic. Key words: COVID-19 Pandemic, Learning Innovation, Learning Loss, Discovey Learning, iNaturalist ABSTRAK Pandemi COVID19 yang terjadi mengakibatkan learning loss pada peserta didik. Permasalahan kehilangan pembelajaran (learning loss) menjadi perhatian dan perlu adanya pemulihan pembelajaran. Penelitian ini bertujuan untuk melakukan inovasi melalui teknologi informasi pada model discovery learning berbantuan aplikasi iNaturalist. Metode penelitian yang digunakan adalah systematic review dengan menggumpulkan bukti untuk menjawab pertanyaan penelitian yang ditentukan. Pengumpulan data pada penelitian ini dengan mereview artikel pada database Google Scholar, SINTA, Scopus dan buku terkait keyword model discovery learning dan aplikasi iNatularistdalam Bahasa Inggris atau Bahasa Indonesia yang terbit pada tahun 2017 hingga 2022. Hasil penelitian menunjukan bahwa inovasi model discovery learning berbantuan aplikasi iNaturalist dapat dilaksanakan dalam pembelajaran sebagai salah satu cara untuk pemulihan pembelajaran pasca pandemi. Kata kunci: Pandemi COVID-19, Inovasi Pembelajaran, Learning Loss, Discovery Learning, iNaturalist